KAJIAN POTENSI KOMODITI UNGGULAN SEKTOR PERTANIAN KABUPATEN KUPANG PROVINSI NUSA TENGGARA TIMUR - M Bas Sri; Ferdi A. Fallo; Blasius Gharu (Partner, 2019)
In the era of regional autonomy, local governments are obliged to plan and control regional economic conditions based on objective conditions. The agricultural sector is a sector that plays an important role in national development. Development planners must maintain superior commodities in the agricultural sector, so that the regional economy can be developed. In addition, the importance of implementing appropriate regional development planning so that it will become a guideline and be able to direct development towards the achievement of objectives made on the basis of commodity bases and the potential base of leading regional agricultural sector. The implementation of regional economic development based on leading commodities in the agricultural sector will be easier to carry out by referring to the results of a study of the potential superior regions. Local governments must also pay attention to non-superior commodities so that they become a sub-system in developing leading agricultural commodities. This study uses the Location Quotient analysis, to find out which commodities are superior in the agricultural sector. The results showed that the leading commodities in the game sector were (1). Food crops consist of (Peanuts, Lading rice and Lowland rice), (2). Vegetable plants consist of (shallots, large chili, tomatoes, cucumbers and cayenne peppers), (3). Fruit plants consist of adri (Soursop, avocado papaya and large grapefruit), (4). and estate crops consist of (Kapok, areca nut and coconut). Keywords: Main commodity, agriculture sector, location quotient, (LQ). Conseil juridique en ligne, son délai de réponse, ses compétences juridiques, Avocat à Paris https://avocats.link/avocat-a-paris/